2022
DOI: 10.3390/nu15010084
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Mediates the Association between Dietary Inflammatory Index and Depressive Symptoms in Breast Cancer

Abstract: This study examined the association between the energy-adjusted Dietary Inflammatory Index (E-DII)-based dietary inflammatory potential and depressive symptoms (DepS) among patients with breast cancer and explores whether systemic inflammation mediates this association. We assessed dietary intake and DepS in 220 breast cancer patients by three 24 h dietary recalls and the Center for Epidemiological Studies Depression Scale (CES-D), respectively, and determined plasma levels of C-reactive protein (CRP), tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The current study found signi cant differences in the average levels of serum cortisol and IL-6 between the depression and non-depression groups, as well as between the anxiety and non-anxiety groups. This nding is in line with previous research indicating that higher levels of TNF-α and IL-6, rather than CRP, were associated with an increased risk of depression in women with breast cancer [20]; however, it is somewhat discrepant to the ndings of Colasanto et al [27], who found signi cant associations between concurrent depression and IL-6 and CRP among children and adolescents and emphasized that a greater proportion of female participants reported stronger effects of concurrent depression and CRP. Despite the fact that all of the patients in this study were women, the association was not signi cant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study found signi cant differences in the average levels of serum cortisol and IL-6 between the depression and non-depression groups, as well as between the anxiety and non-anxiety groups. This nding is in line with previous research indicating that higher levels of TNF-α and IL-6, rather than CRP, were associated with an increased risk of depression in women with breast cancer [20]; however, it is somewhat discrepant to the ndings of Colasanto et al [27], who found signi cant associations between concurrent depression and IL-6 and CRP among children and adolescents and emphasized that a greater proportion of female participants reported stronger effects of concurrent depression and CRP. Despite the fact that all of the patients in this study were women, the association was not signi cant.…”
Section: Discussionsupporting
confidence: 92%
“…IL-6 and TNFα may be more indicative of acute in ammation than CRP. According to a previous study in breast cancer [20], IL-6 and TNF-α may have a greater effect on depression and anxiety. Additionally, some basic studies have reported a daily rhythm of in ammation [21,22].…”
Section: Introductionmentioning
confidence: 93%
“…Pro-inflammatory diets activate the innate sensor cells-recognizing microbe-associated molecular patterns receptor, and this activation can trigger pro-inflammatory cytokines production, including interleukin (IL)-6 and C-reactive protein (CRP) [ 25 27 ]. Several studies have shown that DII is associated with circulating concentrations of CRP, IL-6 and tumor necrosis factor-α [ 28 30 ]. In contrast, the Mediterranean diet, which is rich in unsaturated fatty acids, has anti-inflammatory properties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese patients with early breast cancer, the variation of IL-10, IFNG1 and BDNF is associated with anxiety/depression symptoms [31] .This study suggests that the expression levels of CCNB1, MLPH, PSME1 and RACGAP1, four key genes, are signi cantly correlated with the expression levels of breast cancer progression genes. RACGAP1 and BRIP1 are signi cantly positively correlated (r=0.688), and MLPH and MSH2 are signi cantly negatively correlated (r=-0.404).The higher number of anti-in ammatory cytokine risk alleles, as well as the IL-1P-511T/T genotype, are associated with baseline prevalent depression and one-year follow-up persistent depression, respectively [32] .In ammatory diet is positively related to breast cancer related depression, which may be caused by tumor necrosis factor-α Mediated [33] .This study revealed the speci c signal pathways of four key genes in breast cancer, and explored the potential molecular mechanism of key genes and breast cancer progression.GSVA analysis of breast cancer showed that overexpression of CCNB1 could enrich E2F_ TARGETS, DNA_ REPAIR and other signaling pathways, high expression of MLPH can enrich P53_ PATHWAY, PI3K_ AKT_ MTOR_ Signaling and other signaling pathways; PSME1 can enrich FATTY_ ACID_ METABOLISM, DNA_ REPAIR and other signaling pathways; RACGAP1 can enrich E2F_ TARGETS, G2M_ Signal pathways such as CHECKPOINT.GSEA analysis of breast cancer showed that CCNB1 was mainly enriched in DNA replication, Fanconi anemia pathway, mRNA surveillance pathway and other signaling pathways; MLPH is mainly enriched in signal pathways such as Chemokine signaling pathway, IL-17 signaling pathway, and TNF signaling pathway; PSME1 is mainly enriched in signaling pathways such as Cytosolid DNA sensing pathway, Neoptosis, RIG-I-like receiver signaling pathway, etc,; RACGAP1 is mainly enriched in signaling pathways such as Carbon metabolism, mRNA surveillance pathway, and Pyrimidine metabolism; These four key genes may affect the progress of breast cancer through these pathways.…”
Section: Discussionmentioning
confidence: 97%